The relationship between primary metabolites in reproductive structures of cowpea Vigna unguiculata (Fabaceae: Papilionidae) cultivars and field resistance to the flower bud thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Alabi, O.; Odebiyi, J.; Tamo, Manuele (Springer, 2006)
Preliminary screening of germplasm from the International Institute of Tropical Agriculture (IITA) showed that a number of cowpea Vigna unguiculata (L). Walp. cultivars have potential for resistance to the flower bud thrips, Megalurothrips sjostedti (Trybom). In an earlier study, 10 cultivars from this germplasm were selected and the mechanisms of resistance determined. Therefore, in this study, the basis of resistance operating in the cultivars was elucidated during the first and second planting seasons of 1998. Cowpea cultivars were analysed for primary metabolites (total protein content and glucose contents) to study their relationship with resistance parameters of M. sjostedti under field conditions. Total protein and glucose contents varied significantly (P<0.01) in floral buds and flowers of the different cultivars, while in racemes there were little or no significant differences. Highly significant negative correlation coefficients were obtained between total protein contents in reproductive structures and resistance parameters, especially during the second season, regardless of cowpea cultivar, indicating that quality of total protein content plays a significant role in cowpea resistance to M. sjostedti. Significant (P<0.05) correlation between damage indices and glucose content in Vita 7 and Kpodjiguegue is responsible for their susceptibility to M. sjostedti damage. Furthermore, presence of a unique protein band (20.1 kDa) in Moussa local, Sanzibanili and Sewe cultivars could be associated with resistance to flower bud thrips, regardless of quantity of total protein content in these and other test cultivars. Similarly, the specific band just above the 94 kDa in Vita 7 could be responsible for its susceptibility to M. sjostedti.